DAMPAK CELEBRITY WORSHIP TERHADAP PROBLEMATIC INTERNET USE PADA REMAJA PENGGEMAR K-POP DI MASA PANDEMI COVID-19 - Felicita Mauli; Agustina Agustina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
The COVID-19 pandemic has spread throughout the world, including Indonesia. New regulations had to be made in order to break the chain of spread. People are starting to look for their own hobbies and pleasures to fill their time at home. Fans of Korean Pop (K-Pop) music are also forced to spend their hobbies listening to songs, following their idol's activities, and others at home. The activities of K-Pop fans are forced to be done online and by accessing the internet. The subjects of this research are K-Pop fans. This research is quantitative research that examines the role of celebrity worship variables and problematic internet use. The research participants were young K-Pop fans aged 11-20 years. Celebrity worship is measured using the celebrity attitude scale (CAS), and problematic internet use is measured by the generalized problematic internet use scale 2 (GPIUS 2). The data were processed using simple linear regression. The results of this study are that there is an impact between celebrity worship on problematic internet use in adolescent fans of K-Pop. The impact of celebrity worship on problematic internet use is 10.1% while the other 89.9% is caused by other factors outside this research.